Heterotopic sites of pleomorphic adenoma - Jasmeen Kaur; Manmeet Kaur (Journal of Family Medicine and Primary Care)
The majority of the tumours occurring in minor salivary glands are malignant with only 18% being benign. Among the benign tumours, pleomorphic adenoma is the most common. Although it presents more commonly in the parotid and submandibular glands, it can occur at any site where salivary glands reside. Only 6.4% of cases of pleomorphic adenoma occur in minor salivary glands, e.g. palate, cheeks, lips, para-pharyngeal space, etc. It occurs in females in the fourth or fifth decade. It presents as an asymptomatic and slow-growing mass. The treatment of choice is wide local excision due to the high rate of recurrence and malignant potential. We present rare case reports of two patients. The first case is of a young 18 years female presenting with recurrent neck (anterior triangle) swelling and the second case is of a 46-year-old female presenting with lower lip swelling. In both cases, it was a slow-growing mass and asymptomatic. Cytological examination of the lesion revealed the diagnosis of pleomorphic adenoma. It was completely excised with no post-operative complication. Pleomorphic adenoma, although a common benign neoplasm of major salivary glands, should always be kept as a possibility at the locations of minor salivary glands. As pleomorphic adenoma can transform into a malignant counterpart, therefore early diagnosis and treatment of the lesion can prevent further complications. The prognosis of pleomorphic adenoma is excellent. However, a close follow-up of the patient is required due to the high rate of recurrence.